ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING SERTA PENGARUH PAJAK TERHADAP KEBIJAKAN DIVIDEN - Taufan, Frendy Akhmad; Wahyudi, Sugeng (Faculty of Economics and Business Diponegoro University, 2013)
The purpose of this research was to examine direct and indirect effect of InstitutionalOwnerships, Profitability and Liquidity on Dividend Policy with Capital Structure as an Intervening Variable and the effect of Tax on Dividend Policy. This research was taken as there are differences in the results of previous researches between researches with each other and there is a difference between the empirical data with existing theories.Sampling technique used is purposive sampling. From four hundred and twenty-eight companies according ICMD which were taken twelve non financial companies. Because, it has thecomplete financial statements from the year 2008 up to 2010. The method of analysis used aremultiple regression and path analysis.Using multivariate regression analysis, it is known that Institutional Ownerships and Profitability have negative significant effect on the Dividend Policy. Capital Structure has positive significant effect on Dividend Policy. Profitability has positive significant impact on Capital Structure. Liquidity has negative significant impact on Capital Structure. According Path Analysis, Capital Structure isn’t the Intervening Variable